Student self-support at the University of Minnesota - Umstattd, James Greenleaf, 1896-1988 (College Problems Series., 1932)
Student Self-Support at the University of Minnesota was first published in 1932. This volume reports the results of an investigation conducted under the University Committee on Educational Research. Dr. Umstattd found that 55 per cent of the students enrolled in the University of Minnesota were earning a part or all of their college expenses. His book is a study of the means used by students to support themselves while in college, the employment services rendered by the university, types of students earning their way, amount of money earned, relationship between students and employers, and effect of self-support on scholastic standing, college activities, health, and various other factors. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions.